2000
DOI: 10.1002/(sici)1521-3986(200004)40:1/2<9::aid-ctpp9>3.0.co;2-f
|View full text |Cite
|
Sign up to set email alerts
|

Spectroscopic Studies of Cold Atomic Hydrogen and Deuterium Produced in a Tokamak Edge Plasma

Abstract: Spectroscopic measurements of low‐n Balmer line profiles of atomic hydrogen and deuterium, emitted within the edge region of the TEXTOR‐94 tokamak plasma, have revealed the existence of a class of cold excited atoms, whose probable origin has been ascribed to electron impact‐induced molecular dissociation. Associated with these cold radiators are a second group of ‘lukewarm’ atoms, i.e. atoms heated by elastic collisions with hot protons (deuterons) diffusing outward from the plasma interior, as well as a thir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
76
0

Year Published

2001
2001
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(80 citation statements)
references
References 79 publications
4
76
0
Order By: Relevance
“…As expected, above 12 eV present results do not model experimental results properly. to be the source of anomalously cold H atoms which have been found in a number of hydrogen plasmas (Hey et al 2000, Hey et al 1999, Hey et al 1996, Mertens & Silz 1997. In chapters 7 and 8, however, it will be shown that at higher initial vibrational states, energy differential cross sections will follow the structure of the vibrational level involved.…”
Section: Angular Differential Cross Sectionsmentioning
confidence: 97%
See 3 more Smart Citations
“…As expected, above 12 eV present results do not model experimental results properly. to be the source of anomalously cold H atoms which have been found in a number of hydrogen plasmas (Hey et al 2000, Hey et al 1999, Hey et al 1996, Mertens & Silz 1997. In chapters 7 and 8, however, it will be shown that at higher initial vibrational states, energy differential cross sections will follow the structure of the vibrational level involved.…”
Section: Angular Differential Cross Sectionsmentioning
confidence: 97%
“…In detached divertor plasmas, vibrationally excited molecules increase plasma recombination due to dissociative attachment followed by mutual neutralization and ion conversion. Dissociative recombination, which then destroys the molecular ions present in these cold plasmas, has been found to be a dominant process (Fantz et al 1999, Behringer & Fantz 2000, Hey et al 2000.…”
Section: Overviewmentioning
confidence: 99%
See 2 more Smart Citations
“…They can desorb either in the form of molecules or atoms. Measurements in TEXTOR [1][2][3][4][5][6][7][8] to molecular flux at low carbon temperature. By heating of the test limiter surface the molecular intensity dropped and the intensity of atomic species increased.…”
Section: Introductionmentioning
confidence: 99%